Tarian Ceracap Inai - Khalid Mohamad Nor, 1976- ([Kuala Lumpur] : Istana Budaya, 2013)
History and description of Ceracap Inai dance, originated as a royal court dance famously performed at Kampung Baru Lenga, a village in Muar town, Johor, Malaysia.
Includes bibliographical references (pages 110-112).
In Malay.
Keywords: Folk dancing -- Malaysia; Malay, folk dancing; Dancing -- Malaysia